Wheelchair basketball athletes` perceptions of the coach-athlete relationship - Pomerleau-Fontaine, L.; Bloom, G. A.; Alexander, D. (Adapted Physical Activity Quarterly, 2023)
The majority of research on the coach-athlete relationship has been explored from the perspective of able-bodied athletes. The purpose of this study was to explore wheelchair basketball athletes` perceptions of the coach-athlete relationship. Timelining and semistructured interviews were conducted with six wheelchair basketball athletes, and data were analyzed using a reflexive thematic analysis. Athletes highlighted the important role that parasport coaches played in fostering an enjoyable wheelchair basketball environment and valued coaches who displayed expertise regarding their athletes` equipment and had personal parasport athletic experiences. Additionally, athletes identified personal preferences, including coaches who addressed sex differences and maintained professional relationships at the national level as contributing factors to the coach-athlete relationship. The current results benefit both parasport coaches and athletes by providing a portrayal of coaching behaviors, characteristics, and expertise that not only influence the parasport coach-athlete dyad but also affect the well-being and athletic development of parasport athletes.